Exploring serum and glucocorticoid-regulated kinase 1: A promising target for COVID-19 and atrial fibrillation treatment - Jamal E-Fatima, PhD; Faez Iqbal Khan, PhD; Dakun Lai, PhD (Heart Rhythm O2)
Serum and glucocorticoid-regulated kinase 1 (SGK1) is a serine/threonine kinase that is involved in various cellular pathways, such as ion transport, cell survival, proliferation, and immune responses. Dysregulation of this enzyme is increasingly being associated with the progression of 2 prominent types of diseases, namely viral infections, such as COVID-19, and cardiovascular disorders, such as atrial fibrillation (AF), positioning it as a potential therapeutic target. With regard to coronavirus 2019 (COVID-19), SGK1 detrimentally affects inflammatory pathways and modulates the cytokine storm, leading to lung tissue damage. Considering this dysregulation, researchers are exploring SGK1 inhibition as a potential strategy for mitigating severe COVID-19 outcomes. SGK1 also regulates pumps and ion channels, significantly affecting cardiac performance in AF. This protein is responsible for promoting fibrosis and inflammation in the cardiac tissue, making it a potential target for reducing atrial fibrillation. SGK1 inhibition offers a new avenue for therapeutic targets against both COVID-19 and AF. This review is aimed at providing a comprehensive overview of SGK1 dysregulation in both diseases, underscoring the urgent need for more preclinical and clinical trials to evaluate effective SGK1 inhibitors for patients with coexisting COVID-19 and AF.